Handbook of child and adolescent aggression - Malti, Tina; Rubin, Kenneth H. (New York ; London : Guilford Press, 2018)
"Presenting cutting-edge work from leading scholars, this authoritative handbook reviews the breadth of current knowledge on aggression from infancy through adolescence. The volume explores the forms and functions of aggression and the multiple factors that contribute to its emergence, development, and consequences, including genetic and biological influences, temperament, family dynamics, peer relations, and social inequality. It provides up-to-date perspectives on problems such as disruptive and defiant behaviors, bullying (including cyberbullying), social aggression, and youth violence, and examines relations between aggression and normative social-emotional and social-cognitive development. Identifying important implications for practice and policy, contributors describe effective approaches to screening, assessment, intervention, and prevention in family, school, community, and clinical settings."--
"Aggressive behavior during childhood and adolescence is an important risk factor for later serious and persistent adjustment problems in adulthood, including criminal behavior, school dropout as well as family-related and economic problems. Researchers have thus deployed considerable efforts to uncover what drives individuals to attack and hurt others. Each chapter explores the issue of aggression with an introduction, theoretical considerations, measures and methods, research findings, implications, and future directions"--
Includes bibliographical references and index.
Keywords: Aggressiveness in children; Aggressiveness in adolescence; Developmental psychology